Lesions of the superior labrum anterior-posterior and biceps tendon [Süperior labrum anterior-posterior ve biseps tendonu lezyonlari.] - (:unkn) unknown (My University, 2005)
Biomechanical studies have shown that the biceps tendon and the superior labrum have significant contributions to the glenohumeral stability. Since superior labrum anterior-posterior (SLAP) lesions pose diagnostic difficulties, they should be kept in mind when evaluating a painful shoulder. Although magnetic resonance arthrography is of great use in diagnostic studies, diagnostic arthroscopy is still the best method for these lesions. Treatment may vary depending on the type of the lesion. As our knowledge about the glenohumeral anatomy enhances, success rates of the arthroscopic treatment of SLAP lesions will increase.